PEMBINAAN PENINGKATAN PROGRAM KERJA MELALUI SUPERVISI MANAJERIAL KEPALA SEKOLAH (Studi Kasus di SDN 06 Ujan Mas, Kabupaten Kepahiang) - Wisna Aini (Manajer Pendididikan, 2017)
As a manager, the principal was faced with many tasks that require genuine responsibility for their implementation. The School Action Research was conducted at SD 06 Ujan Mas Kepahiang district and the problems the research were the quality of principals work program by school supervisor through principals managerial supervision who followed with guidance and coaching directly and continuously. In the implementation of this PTS the procedure was to supervise and analyze the principal administration, provide technical guidance on SWOT analysis and ways of compiling annual work program and the direct guiding SWOT analysis and preparation of annual work program of principals.